Axillary neuropathy mimicking quadrilateral space syndrome and its follow up for one year - (:unkn) unknown (RIYADH ARMED FORCES HOSPITAL, 2008)
Axillary neuropathy due to entrapment of the nerve in the quadrilateral space is seen rarely. Here, we describe a 24-year-old patient diagnosed with isolated axillary neuropathy that mimicked quadrilateral space syndrome. Quadrilateral or quadrangular space syndrome (QSS), first described by Cahill and Palmer in 1983, was defined as the entrapment of the distal branch of the axillary nerve and the posterior humeral circumflex artery (PHCA) in the quadrangular shaped anatomic space. We tracked the follow up of the patient for one year both clinically and electrophysiologically. Our aim in reporting this case is to stress the point that cases of such a nature usually represent situations of diagnostic and treatment challenges, where multidisciplinary approaches are required.
Keywords: INJURIES; SHOULDER; SPORTS